(untitled) (Journal of Advanced Research in Social Sciences, 2023)
Southeast Asia (SEA) is geographically divided into two sub-regions, mainland and insular. This region consists of 11 states that consistently oppose social liberal changes and uphold traditional values. Conservatism in politics, economy and society, including the legal realm, is always favoured in this region. However, recent developments in Thailand could test the conservative beliefs and practices in this region. In June 2022, Thailand decriminalised the cultivation and consumption of cannabis. This new law allows people in Thailand to consume marijuana edibles, marijuana-infused drinks and use marijuana for medical purposes. This is not the first time Thailand has liberalised its laws. For example, unlike other SEA countries, Thailand does not regulate the use clothing in private spaces; therefore, there has been a significant increase in the number of clothing-optional resorts in Thailand over recent years. Meanwhile, in 2015, Thailand became the first SEA country to recognise and protect the rights of Lesbian, Gay, Bisexual, and Transgender (LGBT) individuals. Such laws and tolerance have now become part of Thailand’s practices and subculture but remain taboo in other SEA states. Hence, this research has investigated the impact of developments in Thailand’s subculture on the SEA sub-regions, with a particular focus on cannabis law reform. Therefore, this research addresses the primary research question: in the context of ‘weed tourism’, could Thailand’s recent cannabis culture impact other Southeast Asian countries? Due to the infancy of this research, a qualitative and digital ethnographical research method was chosen. The thematic analysis was adopted from the secondary government-published data by eliciting key themes. The findings revealed that weed tourism activities would encourage the people in this region to understand, respect, or even practice Thailand’s subculture themselves. The mainland states may tend to accept and observe Thailand’s cannabis subculture in their states. However, the insular states will not accept such subcultures and will always consider such activities as countercultural.